Islamic Inheritance Law in Indonesia and Malaysia: An Interdisciplinary Study of Conflict, Resolution, and Gender Perspectives - Rini, Etiak (Tasyri' : Journal of Islamic Law, 2026)
This study aims to compare the implementation of Islamic inheritance law in Indonesia and Malaysia, particularly regarding the treatment of women as heirs. Although Islamic inheritance law theoretically grants women equal rights, in practice, the distribution of inheritance is often influenced by social, cultural, and governmental factors. In Indonesia, the strong patriarchal culture and the lack of public understanding of Islamic inheritance law often result in women not receiving their rightful share of inheritance. A similar issue exists in Malaysia, where, despite the Syariah Court's rulings on women's inheritance rights, local customs and policies often lead to women receiving a smaller share or losing their inheritance rights altogether. This study uses a qualitative approach with comparative analysis, relying on data from international journals, related literature, and applicable legal documents in both countries. The results of the study show that while both countries have legal foundations supporting women's rights as heirs, gender inequality in inheritance distribution remains a significant issue that needs to be addressed. Therefore, policy reforms and the strengthening of legal education are necessary to ensure the fair and equal implementation of Islamic inheritance law for women.